Positive coping strategies and performance level among Universiti Sains Malaysia (USM) athletes - Parnabas, Vincent A.; Abdullah, Nagoor Meera; Omar Fauzee, Mohd Sofian; Mohamad Nizam, Nazaruddin (International Journals of Multidisciplinary Research Academy, 2013)
Anxiety is one of the main barriers that impact on performance among athletes and countless researches have been conducted on coping strategy techniques to reduce anxiety among athletes. Coping strategies involve positive or negative techniques. Positive techniques include positive self-talk, physical activity, goal setting, thinking on practice, thought stopping, remembering the worst-case scenario, focus on what you can control, imagery, meditation, simulation, breathing techniques, progressive relaxation, autogenic training and biofeedback, while, negative techniques include drugs, alcohol and smoking.The present study sought to explore potential positive coping techniques used by athletes as influence by demographic variables of athletes.The sample consisted of 78 Universiti Sains Malaysia (USM) athletes. The sample was drawn from athletes who competed in MASUM (Sport between Universities).Results showed that imagery have the highest usage among athletes. National athletes used more postive coping techniques than state, district, and university level athletes.Positive coping techniques of high level performance athletes were more than medium and low level performance athletes.The findings emphasized the importance of positive coping strategies to enhance performance.Sport psychologists, sport counselors and coaches should encourage their athletes to use positive coping strategies to improve performance.